Electronic Medical Record Information System to Support Clinical Management of Web-Based Medical Report Resumes - Putri, Lienda Dwi; Setyawan, Adhita Arif; Yunengsih, Yuyun (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Medical records are important documents that record patient information, including examinations, treatments, actions, and services. Article 46 paragraph (1) of the Medical Practice Law defines medical records as files containing patient identity, examination results, treatments, actions, and other services. Regulation of the Minister of Health No. 21 of 2020 concerning the Integration of Health Information Systems, in the Ministry of Health's Strategic Plan 2020-2024, emphasizes the importance of a fast, accurate, integrated, and electronic-based health information system. This study aims to develop an electronic medical record information system for creating web-based medical resumes, using Visual Studio Code, PHP, MySQL, and Laravel. The development method used is agile. The results of the study show that the application of the agile method in developing web-based medical resumes increases effectiveness and efficiency. The problem identified is manual medical resume writing, which is often illegible, making it less efficient. To overcome this, an electronic medical resume design was developed as part of an electronic medical record system, which allows for faster, timelier, and clearer medical resume creation. This medical resume management system is expected to increase efficiency and readability